Table of Content - -, (Journal of medical and pharmaceutical sciences, 2024)
Table of Content:1. Effect of beetroot extract on glucose-6-phosphate dehydrogenase, red blood cells, and their aggregation in a patient with Hereditary Spherocytosis: A case reportDr. Zahraa S. Al-Garawi, Saif A. Mahnna, Bilal M. Hamed, Ameen Y. Al-Garawi2. Effect of the Degree of canal Moisture on the Fracture Resistance of Endodontically Treated Teeth Roots Using Different Sealers (In Vitro Study)Dr. Alaa Abdulrahman Alomar, Prof. Hassan Alhalabiah3. The Impact of Nurses' Knowledge and Self-Efficacy on Quality of Life and Symptom Burden  for Patients with Gastric Cancer Receiving Palliative Care in Jordan: A Review of LiteratureDr. Nizar Adnan Rfefan Ass’ad4. PCOS: Causes and treatmentDr. Souad Fareg Mohammd Dadoush5. The effect of celecoxib on kidney function in elderly people in the Saudi health sectorDr. Hela Saleh Al-Khulaifi, Nurse \ Tala Saeed Al-Mutairi, Nurse \ Norah Ibrahim Al-Battal
Keywords: Journal of Medical and Pharmaceutical Sciences